MANAJEMEN SUPERVISI KEPALA SEKOLAH: DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK GURU DI SMPN 3 CIPATAT - Supyan Sauri; Dina Hairun Nissa; Dhita Annisa Fauzia; Nina Ambarawati; Ratnawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the importance of teachers' pedagogical competenceas a key pillar of educational quality, which is often hampered by the implementationof supervision that is merely an administrative formality. This study aims to exploreand analyze the supervision management of the principal at SMPN 3 Cipatat inimproving teachers' pedagogical competence, which includes aspects of planning,organizing, implementing, evaluating, and following up. The research method usedwas a qualitative approach with a case study design. Data were collected throughin-depth interviews, participatory observation, and documentation studies. The maininstrument of the study was the researcher himself, with data analysis techniquesfrom Miles, Huberman, and Saldaña, which included data reduction, datapresentation, and conclusion drawing. Data validity was ensured through sourceand technique triangulation. The results showed that supervision management atSMPN 3 Cipatat had been implemented as a systematic and continuous managerialprocess. Planning was carried out collaboratively by developing annual programsbased on teachers' needs. Organization involved the vice principal and seniorteachers to create a friendly professional atmosphere. Implementation follows aclinical supervision cycle consisting of pre-observation, classroom observation, andpost-observation stages through reflective discussion. Evaluation and follow-up arecarried out in the form of individual coaching and internal training. The researchfindings show an increase in the variety of learning methods, improvements ininstructional tools, and the growth of a culture of reflection among teachers. Theconclusion of this study confirms that professionally and humanistically managedsupervision is effective in improving teachers' pedagogical competence and creatinga conducive academic climate.